Quality Assurance Framework for Recovered Binders and Aggregates from Asphalt Mixtures Incorporating Recycled Materials - Eslam Deef-Allah; Magdy Abdelrahman (Recycling)
This study proposes that a proactive quality assurance (QA) framework for asphalt mixes with recycled materials, i.e., reclaimed asphalt pavement and recycled asphalt shingles, should be developed. Quality control (QC) is generally concerned with the contractor’s obligation to produce mixes which meet the job mix formula (JMF) targets. However, QA considers the variability in fabrication processes and materials and offers monitoring by evaluating the contractor’s performance. Although both aggregate gradations and asphalt contents were within the JMF specifications, the recovered binders revealed significant differences from the contract binders in the JMF. Rheological tests indicated increased stiffness and elasticity but reduced capability to relax thermal stresses in binders recovered from plant–lab- and lab-fabricated mixtures, compared to field mixtures. Thermal-rheological analysis models corroborated these results by demonstrating reduced decomposition areas for more aged binders, enhancing performance prediction—especially for limited binder amounts. The creation of a QA decision matrix facilitated uniform, performance-oriented assessments. The matrix indicated only 23% of the mixtures satisfied JMF criteria and reported QC data—predominantly field mixtures—underscoring the impact of the fabrication mechanisms and the use of soft binders. This matrix integrates statistical analysis and binder performance assessments as a tool for verifying material compliance and tracking contractor efficiency. It reflects a transition from traditional QC toward a more proactive QA framework for sustainable pavements.